Trophic Status and Community Structure of Phytoplankton in Lake Beratan, Candikuning Village, Baturiti Subdistrict, Tabanan District, Bali Province - Ananda, Yuli; Restu, I Wayan; Ekawaty, Rani (Metamorfosa: Journal of Biological Sciences, 2019)
Beratan Lake is located in Bedugul, Candikuning Village, Baturiti Subdistrict, Tabanan District, Bali Province. Beratan Lake is a caldera lake with a surface area of 438 hectares, 1,340 hectares of water catchment areas,  a length of 2 km and 2 km wide and 49.22 million m 3 of water volume. This research was conducted in January until February 2016. The aims of this study are to phytoplankton community structure.The composition of phytoplankton were found during this study  dominated by  the phylum of Chlorophyta and species were often found with high abundance is Staurastrum tetracerum . Average abundance in the waters of Lake Beratan is in the range 2054-2502 ind/l which shows that the waters of Lake Beratan with moderate fertility (mesotrophic). The value of species diversity (H ') has ranges from 2,34 - 2,55. The range uniformity index values has from 0.76 - 0.83. Value index of phytoplankton dominance has range of 0,1- 0,16 dominance relatively low indicated the absence of certain species dominance.